Nutritive value of palm oil sludge and its influence on fat composition and deposition in grower pigs - Adebiyi, O.A; Oboli, U.T; Adejumo, I.O; Osinowo, O.A; Olumide, Martha; Adeshola, A.T (Nigerian Journal of Animal Science, 2023)
Globally, pig is the main species for meat consumption. Meat animals are manipulated for reduced lipid deposition in order to enhance their production efficiency while improving meat quality. Grower pigs (n = 40) were randomly allotted to four compounded dietary treatments having 0%, 10%, 20% and 30% processed palm oil sludge (POS) replacing maize respectively. Growth response and lipid profile of the animals were determined using standard protocols. POS-based diets compared with the control group for growth response. The POS lowered low-density lipoproteins, the reduction was more pronounced for 20% and 30% POS inclusion level having 18.15 mg/dl and 19.60 mg/dl respectively. 30% POS inclusion increased high-density lipoprotein concentration (38.00 mg/dl), while 10% and 20% POS inclusion compared well with the control group. POS could be said to enhance the quality of pork meat for human consumption. This study may further be developed towards controlling some cardiovascular diseases in human.